Variability of ankle movements as a fatigue factor in runners - Negodenko, E. S.; Medvedeva, E. V.; Kapilevich, L. V. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to assess the stability of the ankle trajectory in runners of various qualifications under conditions of fatigue.